Conservative Ideas in Pedagogical Thinking of Phenomenologist Ján Patočka and Personalist Ladislav Hanus - Mária Potočárová (Jagiellonian University Press, 2023)
In this paper we focus on the reflection of conservative ideas reflected in pedagogical thinking. The conservative trend in the philosophy of education is presented in a selection of two representatives from the environment of the former Czechoslovakia, who lived and were active in the period of totalitarian real socialism. We present the philosopher and phenomenologist Ján Patočka and the personalist and theologian Ladislav Hanus. Both of them are united by the fact that their works are based on the common philosophical direction of phenomenology and existentialism. In addition, both representatives, above all, through their personal life stories, have been committed to humanistic and conservative values, for which they had to endure persecution during the totalitarian period. They tried to pass on their convictions through the formation, upbringing and education of the younger generation. This common purpose also linked them to pedagogy, to the development of philosophical pedagogical thinking. This article will compare the philosophical views of both, as well as the personalistic and anthropological conceptions of society that were rooted in phenomenology as well as in the tradition of Christian humanism. The contribution of the life and work of J. Patočka and L. Hanus remains significant for contemporary pedagogy and philosophy of education. The paper has also attempted to add some of the basic knowledge of philosophy of education needed in the education of future teachers. ABSTRAKT  Idee konserwatywne w myśleniu pedagogicznym fenomenologa Jána Patočki i personalisty Ladislava Hanusa W niniejszym artykule koncentruję się na refleksji nad ideami konserwatywnymi odzwierciedlonymi w myśleniu pedagogicznym. Nurt konserwatywny w filozofii wychowania prezentuję na przykładzie dwóch przedstawicieli ze środowiska byłej Czechosłowacji, którzy żyli i działali w okresie realnego socjalizmu. Przedstawiam filozofa i fenomenologa Jána Patočkę oraz personalistę i teologa Ladislava Hanusa. Obu łączy to, że ich prace opierają się na wspólnym kierunku filozoficznym fenomenologii i egzystencjalizmu. Ponadto obaj przedstawiciele, przede wszystkim poprzez swoje osobiste życiorysy, oddali się humanistycznym i konserwatywnym wartościom, za które musieli znosić prześladowania w okresie totalitarnym. Swoje przekonania starali się przekazywać poprzez formację, wychowanie i edukację młodego pokolenia. Ten wspólny cel łączył ich również z pedagogiką, z rozwojem filozoficznej myśli pedagogicznej. W niniejszym artykule porównuję poglądy filozoficzne obu, a także personalistyczne i antropologiczne koncepcje społeczeństwa, które były zakorzenione w fenomenologii oraz w tradycji humanizmu chrześcijańskiego. Wkład życia i twórczości J. Patočki i L. Hanusa pozostaje istotny dla współczesnej pedagogiki i filozofii wychowania. W artykule podjmuję również próbę uzupełnienia podstawowej wiedzy z zakresu filozofii edukacji, potrzebnej w kształceniu przyszłych nauczycieli.